2021
DOI: 10.1093/bjc/azab031
|View full text |Cite
|
Sign up to set email alerts
|

‘Covid-19 has caused a dramatic change to prison life’. Analysing the impacts of the Covid-19 pandemic on the pains of imprisonment in the Scottish Prison Estate

Abstract: The purpose of this paper is to provide insights into the impact of COVID-19 in the Scottish Prison Estate. During the 2020 lockdown in prison in response to the COVID-19 pandemic, all face-to-face research was paused. In response to this methodological challenge, a participatory correspondence methodology was designed, enabling project participants to influence the direction of this project through suggesting research questions. The main project findings relate to the analysis of ways in which the COVID-19 en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 42 publications
(36 reference statements)
2
56
0
Order By: Relevance
“…It has been suggested that the pandemic and associated preventive measures (e.g., physical distancing) have reinforced symptom severity and psychosocial stress in those with psychiatric disorders ( Favreau et al, 2021 ; Quittkat et al, 2020 ) and intensified ageism ( Cohn-Schwartz and Ayalon, 2021 ; Swift and Chasteen, 2021 ). Also, it has exacerbated challenges faced by justice-involved populations at correctional and forensic psychiatric settings (e.g., detachment and limited communication with family and friends) and upon reentering the society (e.g., increased suicide risk) ( Kennedy et al, 2020 ; Maycock, 2021 ; Mitchell et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the pandemic and associated preventive measures (e.g., physical distancing) have reinforced symptom severity and psychosocial stress in those with psychiatric disorders ( Favreau et al, 2021 ; Quittkat et al, 2020 ) and intensified ageism ( Cohn-Schwartz and Ayalon, 2021 ; Swift and Chasteen, 2021 ). Also, it has exacerbated challenges faced by justice-involved populations at correctional and forensic psychiatric settings (e.g., detachment and limited communication with family and friends) and upon reentering the society (e.g., increased suicide risk) ( Kennedy et al, 2020 ; Maycock, 2021 ; Mitchell et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, with prisoners often disproportionately representative of the most deprived in society, the families of these prisoners may not have access to the appropriate technology to enable them to utilise video or virtual visitation procedures; especially since facilities like libraries and internet cafes are also impacted by the outbreak of the virus, further limiting accessibility (Robinson et al, 2020). A recent scoping review of the mental health implications of the Covid-19 pandemic within prison settings suggests that this has caused challenges to prisoner mental health (Johnson et al, 2021), this is also reflected in the associated papers in this study (Maycock, 2021;Maycock & Dickson, 2021). Importantly, this scoping review also indicates that existing research in relation to the impacts of Covid-19 in relation to mental health of prisoners is quite limited:…”
Section: Covid-19 In Prison Settingsmentioning
confidence: 87%
“…In terms of qualitative research on Covid-19 more widely, the responses to letter two shaped later correspondence between the PI and participants, reported elsewhere (Maycock, 2021;Maycock & Dickson, 2021), and it is hoped that the letters that came after letter two were ones that resonated with areas that the participants felt were important. In this sense, we can clearly see the impacts of the participants responses analysed in this paper in relation to the direction of the research project from letter two onwards.…”
Section: Conclusion -To What Extent Can Qualitative Correspondence Me...mentioning
confidence: 94%
See 1 more Smart Citation
“…The COVID-19 emergency amplified social disadvantage and exalted the contexts of vulnerability, 33 which imposed on states the obligation to prepare and respond to the social crisis. In other words, the greater the risk for the individual, the greater the degree of vulnerability -and the greater effort is required for national authorities to support the weakest subjects.…”
Section: Victims Of Domestic Violencementioning
confidence: 99%